Formation of a Secretion-Competent Protein Complex by a Dynamic Wrap-around Binding Mechanism. Issue 18 (14th September 2018) - Gupta, Arun A.; Reinartz, Ines; Karunanithy, Gogulan; Spilotros, Alessandro; Jonna, Venkateswara Rao; Hofer, Anders; Svergun, Dmitri I.; Baldwin, Andrew J.; Schug, Alexander; Wolf-Watz, Magnus
Abstract: Bacterial virulence is typically initiated by translocation of effector or toxic proteins across host cell membranes. A class of gram-negative pathogenic bacteria including Yersinia pseudotuberculosis and Yersinia pestis accomplishes this objective with a protein assembly called the type III secretion system. Yersinia effector proteins (Yop) are presented to the translocation apparatus through formation of specific complexes with their cognate chaperones (Syc). In the complexes where the structure is available, the Yops are extended and wrap around their cognate chaperone. This structural architecture enables secretion of the Yop from the bacterium in early stages of translocation. It has been shown previously that the chaperone-binding domain of YopE is disordered in its isolation but becomes substantially more ordered in its wrap-around complex with its chaperone SycE. Here, by means of NMR spectroscopy, small-angle X-ray scattering and molecular modeling, we demonstrate that while the free chaperone-binding domain of YopH (YopH CBD ) adopts a fully ordered and globular fold, it populates an elongated, wrap-around conformation when it engages in a specific complex with its chaperone SycH2 . Hence, in contrast to YopE that is unstructured in its free state, YopH transits from a globular free state to an elongated chaperone-bound state. We demonstrate that a sparsely populated YopH CBD state has an elevated affinity for SycH2 and represents an intermediate in the formation of the protein complex. Our results suggest that Yersinia has evolved a binding mechanism where SycH2 passively stimulates an elongated YopH conformation that is presented to the type III secretion system in a secretion-competent conformation. Graphical abstract: Unlabelled Image Highlights: Yersinia pseudotuberculosis translocates effector proteins into eukaryotic host cells. The effector YopH was found to make a high-affinity complex with its cognate chaperone. YopH wraps around the chaperone in the protein complex. An on-pathway YopH intermediate crucial for chaperone binding was identified. YopH transits from a globular to an extended conformation upon chaperone interaction.